A study on the factors that affect individual’s performance: A case study at Department of Natural Resources and Environment, Ayer Keroh Melaka / Shafinaz Mad Safri and Sharifah Shafiqah Syed Salim - Mad Safri, Shafinaz; Syed Salim, Sharifah Shafiqah (Faculty of Administrative Science and Policy Studies, 2013)
This research is about a study on the factors that affect individual’s performance in Department of Natural Resources and Environment, Ayer Keroh Melaka. The objectives of this research are to measure the level of individual performance, to measure the level of factors that affect an individual performance, and to determine the relationship between efforts motivation, skills ability, role perceptions, and organization resources with individual’s performance. 50 respondents were selected as a sample size of this research. Simple random sampling technique was used when selected the 50 respondents at Department of Natural Resources and Environment at Ayer Keroh Melaka. The respondents were required to answer questionnaire that consist of 3 sections with 62 questions. The researcher use Descriptive Statistic, Cronbach’s Alpha and Peason Rank Order Correlation to analyze the data gathered by using Statistical Package for Social Science (SPSS) version 20.0. The result indicates that the level of individual performance is good and the employees agreed that they have a good level of effort motivation, skills and ability, role perceptions, and organizational resources. In addition, there are positive correlation between all four factors which are efforts motivation, skills ability, role perceptions, and organizational resources with individual’s performance. The most influential factor that affects individual performance in Department of Natural Resources and Environment at Ayer Keroh, Melaka is skills and ability with the significant value in regression test is 0.020.